Hemispheric Organization of Visual Word Recognition in Turkish Monolinguals - Filiz Mergen; Gulmira Kuruoglu (Психолінгвістика, 2019)
Recently obtained data from interdisciplinary research has expanded our knowledge on the relationship between language and the brain considerably. Numerous aspects of language have been the subject of research. Visual word recognition is a temporal process which starts with recognizing the physical features of words and matching them with potential candidates in the mental lexicon. Word frequency plays a significant role in this process. Other factors are the similarities in spelling and pronunciation, and whether words have meanings or are simply letter strings. The emotional load of the words is another factor that deserves a closer inspection as an overwhelming amount of evidence supports the privileged status of emotions both in verbal and nonverbal tasks. It is well-established that lexical processing is handled by the involvement of the brain hemispheres to varying degrees, and that the left hemisphere has greater involvement in verbal tasks as compared to the right hemisphere. Also, the emotional load of the verbal stimuli affects the specialized roles of the brain hemispheres in lexical processing.